Economic and Legal Support of Employee of Employee-Shared Ownership in Modern Russia: Regions’ Opinion - GABDULHAKOVA, Olga Ivanovna; NEKRASOVA, Olga Vladimirovna (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
Currently in Russia, a great part of capital is steadily formed in a small number of people. Unfortunately, this model of capital concentration cannot be considered effective nor called socially equitable for the majority of the population. The difficult state of domestic production in all regions of the country, the negative impact of general political developments in the world and other factors contribute neither to the increase in the productivity of enterprises, nor to the increase in the employee’s interest to improve the profitability of enterprises, nor to the growth of the Russian economy as a whole. It is therefore necessary to consider alternative ways of development of the modern economy, to raise the interest of each employee (not only the owner, shareholder or senior management) of enterprises in the end result of their activity. In our opinion, an alternative form of society capitalization is the development of employee-shared ownership. This experience is especially prevalent today in many countries with successful economies. In Russia, this ownership exists in the form of a few public enterprises (employee-owned closed joint-stock companies). This paper considers the question of the attitude of the country’s regions to the functioning and dissemination of the experience of enterprises with employee stock ownership in the current Russian economic reality.